Some Properties of Rough Ideals on Rough Rings - Fakhry Asad Agusfrianto; Lukita Ambarwati (Eigen Mathematics Journal, 2023)
The concept of rough set was first introduced by Pawlak in 1982. The basic concepts in set theory such as intersections, unions, differences, and complements still apply to rough sets. Furthermore, researchers in the field of mathematics and informatics who study rough sets can relate the concept of rough sets to algebraic structures so that a concept called rough algebraic structures is obtained. Some concepts on rough algebraic structures are rough groups, rough rings, and rough modules. In this paper, the properties related to the ideal of roughness will be given to the rough ring.